Molecular cloning of human epsilon-globin gene. - Proudfoot, N; Baralle, F (1979)
Human beta-like globin genes were investigated by use of rabbit beta-globin cDNA plasmid as a cross-species hybridization probe. Normal and beta 0/delta beta 0 thalassemic DNA were compared by filter hybridization procedures. It proved possible to demonstrate that the rabbit probe detected G gamma, A gamma, delta, beta, beta 0, and delta beta 0 human globin genes as well as an additional unidentified beta-like globin gene. By use of an agarose gel elution procedure, fractions of HindIII-digested DNA enriched for beta-like globin genes were purified. One of these fractions, 8.0 kilobases in size, was clonedinto lambda 788, and EK2 lambda HindIII vector. A positive clone was obtained and characterized by restriction mapping and sequence analysis. The sequence data obtained predicted an amino acid sequence that exactly matches a part of human epsilon-globin. The human non-alpha-globin locus is now nearly complete. delta, beta, and gamma human globin genes have already been cloned and analyzed. We describe here the cloning of the remaining non-alpha-globin gene, epsilon.